2019
DOI: 10.3390/ijerph16152781
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Hospitalization for Dementia in Urban China: Estimates from Two Urban Health Insurance Scheme Claims Data in Guangzhou City

Abstract: Background: Dementia is one of the public health priorities in China. This study aimed to examine the hospitalization costs of patients with dementia and analyzed the factors associated with their inpatient costs. Methods: This was a prevalence-based, observational study using claims data derived from two urban insurance schemes during the period from 2008 through 2013 in Guangzhou. The extended estimating equations model was performed to identify the main drivers of total inpatient costs. Results: We identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 42 publications
(74 reference statements)
3
11
0
Order By: Relevance
“…The regression analysis also found that the type of health insurance (UEBMI) was significantly correlated with higher inpatient costs of PD patients. These findings were consistent with prior studies exploring disparities in medical costs of patients with other diseases between these two types of health insurance schemes in China [ 34 , 35 , 48 ]. The possible explanations were discussed as follows.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The regression analysis also found that the type of health insurance (UEBMI) was significantly correlated with higher inpatient costs of PD patients. These findings were consistent with prior studies exploring disparities in medical costs of patients with other diseases between these two types of health insurance schemes in China [ 34 , 35 , 48 ]. The possible explanations were discussed as follows.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the administrative restrictions on accessing the social insurance claims database, this was the most recent data available for this study. The UEBMI and URBMI are two social health insurance schemes covering the population of urban employees and urban non-employed residents in Guangzhou City, with a great deal of differences in service coverages and reimbursement rates [ 34 , 35 ]. The detailed comparisons of UEBMI and URBMI policies for PD patients in Guangzhou City were summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations